Interobserver variability in histological diagnosis of serrated colorectal polyps - Baldin,Rosimeri Kuhl Svoboda (2015)
Objectives: To compare the interobserver variability in the diagnostic of serrated and non- serrated adenomatous lesions and hyperplastic polyps of colon between two groups of pathologists. Methods: 310 colorectal polyps were studied, with histological diagnoses established by a group of pathologists comprising three general pathologists for initial diagnosis, and two gastrointestinal pathologists for expert diagnosis. Results: High interobserver variability was observed in the diagnosis of serrated polyps, when comparing the initial diagnosis with the expert diagnosis (kappa = 0.102). For the majority of both traditional serrated adenomas and sessile serrated adenomas (27/31), a diagnosis of hyperplastic polyps was established at the initial diagnosis. Conclusions: Poor agreement was observed in the diagnosis of serrated polyps between the two groups of pathologists. The accuracy in the diagnosis of these lesions is essential for the prevention of colorectal cancer.